Draw the complexity. The diagram in artistic research within the academy - Horcajada González, Ricardo (Nawi, 2023)
Since the beginning of the 21st century, the epistemological shift in academic research towards the visual has forced researchers in all areas to provide themselves with tools and strategies that facilitate the visual transfer of large amounts of information. One of the most effective systems is the diagram. Our proposal is to conceive the diagram, in a summary way, in all its magnitude and possibility. Both as a system of synthesis in transfer and as a speculative space where complex cognitive processes interact. This process of cognitive modelling through drawing generates a speculative framework built by means of skills and knowledge specific to our area. In this article we summarise the main modes and aspects of the diagram as a graphic process of cognitive modelling.